Icnofósseis da Formação Alter do Chão (Grupo Javari, Bacia do Amazonas) em Ponta das Lajes, Manaus (AM): classificação e inferências Paleoambientais - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
In rocks with low occurrence of body fossils, paleontological studies focused on the classification and paleoecological survey of ichnofossils may be an important alternative to obtain information about the rocks sedimentation conditions and its paleoenvironments. So, as the Alter do Chão Formation (Javari Group, Cretaceous Amazon Basin) is admittedly poor in body fossils, the development of integrated sedimentological and paleontological studies based on ichnofossils show be a potential tool for this purpose. These fossils occur in an outcrop located on the left marge of the Rio Negro, Manaus - AM, known as Ponta das Lajes and the lithology is predominantly composed of sandstones, siltstones, clay and conglomerates. The faciological analysis of these rocks led to the recognize eight lithofacies related to three facies associations, wich were interpreted as representative of channel fill deposits, floodplain lake and splay crevasse. The paleontological study of ichnofossils was developed from the morphological comparison of the selected material with description of Mesozoic continental ichnofossils. As a result, two ichnocategories were identified – burrows and root marks (rhizoliths). The analysis of burrows was directed mainly to the formation processes and to the identification of the producing animal, here interpreted as aestivation burrows of dipnoic fish (lungfishes). In turn, the analysis of the root marks structures (rhizoliths) was directed to its paleoenvironmental meaning from categorization of three categories of rhizoliths – rhizoconcretions, root tubules and root casts. Finally, the integration of the results obtained by sedimentary facies analysis and the classification of ichnofossils shows that the sub-environments identified in this sequence are associated with a fluvial system, possibly with braided pattern with moderate to high sinuosity.
Ichnofossils of Alter do Chão formation (Javari Group, Amazon Basin) in Ponta das Lajes, Manaus (AM): paleoenvironmental inferences and classification
Keywords: Icnologia; Paleontologia - Cretáceo; Iconofósseis; Fósseis corpóreos; Formação Alter do Chão; CIÊNCIAS EXATAS E DA TERRA: GEOCIÊNCIAS; Icnologia; Paleoambientes; Formação Alter do Chão; Bacia do Amazonas